Investigation of components of the mRNA methylation complex in arabidopsis - Albalawi, Doha (2020)
N6-methyl-adenosine (m6A) is the most abundant internal mRNA modification and is critical to the development of many eukaryotic organisms, being involved in many different biological processes. The formation of this modification is catalysed by the methyltransferase (MTase) “writer” complex. A core set of mRNA m6A writer proteins in Arabidopsis thaliana includes MTA (METTL3), MTB (METTL14), FIP37 (WTAP), VIRILIZER (VIRMA) and the E3 ubiquitin ligase HAKAI. In this study, we aim to elucidate the role and regulation of MTB in mRNA methylation in Arabidopsis through mutant characterization, complementation and promoter studies. Different approaches were adopted in order to establish stable lines with reduced MTB expression, thus allowing the functional role of MTB during Arabidopsis development to be investigated. Firstly, we identified two heterozygous T-DNA insertion mutants of MTB. Plants containing either of these T-DNA insertions could only be isolated as heterozygous, the homozygous knockout in MTB resulted in embryo lethality and the seeds had an embryo lethal phenotype. In order to rescue the homozygous embryo lethal mutation phenotype, the transgenic plants that contained the T-DNA insertion (SALK-056904) were crossed with plants containing MTB transgene under the control of a seed-specific promoter. The homozygous plants obtained using this approach showed developmental defect phenotypes similar to but more severe than either MTA, FIP37 or Virilizer knockdowns (which have a reduction of m6A level by more than 80% compared with that in WT). In a further approach to investigate the function of the MTB protein, versions of MTB in which the S-adenosylmethionine (SAM) binding domain (methyl donor) has been mutated were generated (MTBΔSAM) for use in overexpression and complementation studies and then compared with previous similar MTAΔSAM results. The Northern blotting analyses confirmed the overexpression of both MTBΔSAM and MTAΔSAM, but only those plants expressing the MTAΔSAM construct gave rise to a dominant negative phenotype with reduced m6A, whereas MTB mutants more closely resembled WT. Moreover, this project also sought to investigate the interaction between MTB and two arginine methylases via yeast two-hybrid (Y2H). In a previous study, the PRMT4a and PRMT4b (a pair of Arginine methyltransferases in Arabidopsis) were found to interact with MTB methylase in Y2H assay, and from proteomics data 4 methylated arginine sites were found in MTB. A construct of MTB-lysine in which the four known sites of arginine methylation are replaced with lysine was generated and used in Y2H. We confirmed the weak interaction between MTB and PRMT4a and PRMT4b via Yeast two-hybrid analysis. Further mutant crosses with, and m6A measurements in, the prmt4a/b double mutant sought to investigate the importance of MTB arginine methylation in m6A writing. Collectively, our findings suggest that MTB is required for embryogenesis, development and normal growth patterns in plants, apical dominance, is involved in regulating trichome morphology and is necessary for full m6A mRNA methylation and our results could pave the way to start studying the interaction between RNA methylation and Arginine methylation in plants and other organisms.